PERBEDAAN KADAR HAEMOGLOBIN SEBELUM DAN SESUDAH KONSUMSI TELUR AYAM NEGERI REBUS PADA IBU HAMIL TRIMESTER III - Gina Nafsa Mutmaina; Desy Syswianti; Meti Rizki Utari; Destira Syalwa Fitria (Fakultas Ilmu Kesehatan Unsika, 2022)
Background Pregnant women are a group of people prone to anemia which is characterized by a decrease in hemoglobin levels, one of the causes of which is iron deficiency in the body. Low absorption of iron in the body can be caused by poor diet, frequency of meals, and amount and type of food consumed. Adequate consumption of animal and plant foods can increase iron intake in the body. One chicken egg contains 6.3 mg of iron in the yolk and 0.2 mg in the egg white. This study aims to determine differences in hemoglobin levels in third-trimester pregnant women before and after consuming boiled chicken eggs. Methods The research was conducted using a quasi-experimental design method with a one-group pretest post-test design approach. The results showed that the average hemoglobin level before consuming boiled chicken eggs was around 11.5 g/dL and the hemoglobin level after finishing boiled chicken eggs was 12.7 g/dL and based on the t-test results, the p-value < 0.001 means differences in hemoglobin levels before and after consuming boiled domestic chicken eggs in third-trimester pregnant women. Keywords: Domestic chicken egg, hemoglobin, pregnant women.